2020
DOI: 10.3389/fpsyg.2020.583324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients Seeking Treatment for Common Mental Disorders Presenting With Workplace Bullying Experiences

Abstract: Background: Targets of workplace bullying tend to develop severe mental health complaints, having increased risk of sick leave and expulsion from the workplace. Hence, these individuals are likely to be overrepresented among patients seeking treatment for common mental disorders (CMD). This study investigated the prevalence of exposure to workplace bullying in a patient group seeking treatment for CMD. Further we explored if exposed and non-exposed patients differed on clinical and workrelated characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
2
7
0
2
Order By: Relevance
“…The patients were diagnosed by the clinical psychologists and psychiatrist responsible for treatment diagnoses in accordance with the national guidelines for assessment in secondary care and the International Classification of Diseases- 10 48) . As previously reported in Aarestad et al 49) , the two most common psychiatric diagnosis among the patients where major depressive disorder and generalised anxiety disorder. In the sample 48.3% of the patients were fully working, 24.1% were on full sick leave, and 27.6% were combining work and partial sick leave.…”
Section: Participants and Proceduressupporting
confidence: 60%
See 2 more Smart Citations
“…The patients were diagnosed by the clinical psychologists and psychiatrist responsible for treatment diagnoses in accordance with the national guidelines for assessment in secondary care and the International Classification of Diseases- 10 48) . As previously reported in Aarestad et al 49) , the two most common psychiatric diagnosis among the patients where major depressive disorder and generalised anxiety disorder. In the sample 48.3% of the patients were fully working, 24.1% were on full sick leave, and 27.6% were combining work and partial sick leave.…”
Section: Participants and Proceduressupporting
confidence: 60%
“…The patients had a number of different occupations, but a majority belonged to occupations classified by the Norwegian standard classification of occupations as professionals (e.g., engineering, health or teaching professions) followed by the category managers. For more information about the sample please see Aarestad et al 49) .…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Two participants had experienced bullying and harassment at work and had not returned for this reason. Previous research has shown that patients exposed to bullying report significantly higher levels of depressive and anxiety symptoms, as well as lower levels of self-efficacy, job satisfaction and have higher prevalence of sick leave [34]. These patients may need more time to return fully to work, as doing so often involves finding a new workplace, which normally may require more time.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to workplace bullying has been documented as a prevalent problem in contemporary workplaces and as a serious threat to the health and well-being of those exposed, being related to a range of mental health problems, as well as self-reported psychosomatic and musculoskeletal complaints [5][6][7][8]. Although physical and psychosomatic outcomes have been studied to a lesser degree than psychological outcomes in the form of anxiety and depression, a number of studies describe elevated levels of self-reported musculoskeletal complaints in targets.…”
Section: Introductionmentioning
confidence: 99%